Reflections of Local Learning Environments on Secondary School Students: The Wastewater Treatment Plant - Cuneyd Celik; Güliz Aydin (Universitas Pendidikan Indonesia, 2024)
The purpose of the current study is to reveal the reflections of the Köyceğiz Wastewater Treatment Plant (WTP) field trip planned within the context of the unit